Estimation of parameters of the beta-extreme value distribution - Zafar Iqbal; M. Aleem (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2008)
In this research paper The Beta Extreme Value Type (III) distribution which is developed by Zafar and Aleem (2007) is considered and parameters are estimated by using moments of the Beta-Extreme Value (Type III) Distribution when the parameters "m" & "n" are real and moments of the Beta-Extreme Value (Type III) Distribution when the parameters "m" & "n" are integers and then a Comparison between rth moments about origin when parameters are "m" & "n" are real and when parameters are "m" & "n" are integers. At the end second method, method of Maximum Likelihood is used to estimate the unknown parameters of the Beta Extreme Value Type (III) distribution.
Keywords: 330